Omnisubjectivity and Classical Theism Are Not Compatible - Mullins, R. T. (Roczniki Filozoficzne, 2025)
Linda Zagzebski argues that omnisubjectivity is compatible with a classical theistic model of God. In this paper I argue that omnisubjectivity is not possibly compatible with classical theism. In particular, omnisubjectivity is in conflict with timelessness, immutability, simplicity, and impassibility.